Dissipation in quantum time dependent mean field - Slama, N.; Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Journal of Physics: Conference Series, 2014)
We discuss an extension of Time dependent (TD) mean field theories such as TD Hartree Fock (TDHF) or TD Kohn-Sham (TDKS) in order to include dissipative effects as observed in many experimental situations. Applications to molecular problems are outlined. We present in particular a 1D model allowing to test a promising approach to include dissipative features in a quantum time dependent mean field. First results are presented in schematic cases. © Published under licence by IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-07-24